Agricultural exports, agricultural imports and economic growth: evidence from China - Sayef Bakari; Sofien Tiba (Agricultural Economics Research Review, 2023)
China’s agricultural exports have been growing rapidly. This paper aims to answer the question whether agricultural trade promotes economic growth. Our findings show that domestic investment and agricultural exports have a positive impact on long-term economic growth. However, agricultural imports had a significant negative impact on economic growth.